Peningkatan Pemahaman Kesehatan Lingkungan Dan Keselamatan Kesehatan Kerja Melalui Kunjungan Edukatif Ke PT Sumatera Deli Lestari Indah - Annisa Febriana Siregar; Solihin; Dhea Amanda Putri (STIKES Columbia Asia Medan, 2025)
Environmental health and occupational safety issues are important aspects in efforts to maintain environmental health and safety for workers in industrial areas. This study aims to improve understanding of environmental health and occupational safety through educational visits to PT Sumatera Deli Lestari Indah. The method used was educational participatory observation of workers at PT Sumatera Deli Lestari Indah. The results of the study indicate that most workers already have basic knowledge about environmental health and Occupational Health and Safety (OHS), but there are still gaps in implementation, such as the use of personal protective equipment (PPE) and inconsistent monitoring of environmental health. Therefore, this activity provides a more comprehensive understanding and encourages healthier work behavior. The expected outcomes of this activity are not only improved worker knowledge but also changes in attitudes and work habits that prioritize health and safety. In the long term, this activity is expected to contribute to improved workplace environmental quality and worker productivity at PT Sumatera Deli Lestari Indah.